Cui bono? The selective revealing of knowledge and its implications for innovative activity - ALEXY, Oliver (Institutional Knowledge at Singapore Management University, 2013)
Current theories of how organizations harness knowledge for innovative activity cannot convincingly explain emergent practices whereby firms selectively reveal knowledge to their advantage. We conceive of selective revealing as a strategic mechanism to reshape the collaborative behavior of other actors in a firm's innovation ecosystem. We propose that selective revealing may provide an effective alternative to known collaboration mechanisms, particularly under conditions of high partner uncertainty, high coordination costs, and unwilling potential collaborators. We specify conditions when firms are more likely to reveal knowledge and highlight some boundary conditions for competitor reciprocity. We elaborate on strategies that allow firms to exhibit managerial agency in selective revealing and discuss selective revealing's implications for theories of organization and open innovation and for management practice.